A method of measurement of directivity characteristics of antenna’s elements for digital antenna array in conditions of jammers - Slyusar, V. I.; Voloshko, S. V. (Видавництво Національного університету "Львівська політехніка", 2009)
A new two-stage digital processing of OFDM signals for measurement of directivity characteristics (DC) of antenna elements in digital antenna array (DAA) with test sources is described in this report.
Keywords: digital antenna array (DAA); digital beamforming; directivity characteristics (DC); OFDM